1990
DOI: 10.1300/j082v19n04_07
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sexual Orientation on Career Decision-Making:

Abstract: This study investigates differences between heterosexuals and homosexuals of both sexes with regard to several variables in the career decision-making process: anxiety about making a career choice, indecisiveness about the choice, need to acquire information about the career of choice, uncertainty about the choice, and career choice dissatisfaction. Significant interactions are found on choice uncertainty (gay men having the highest level of uncertainty and lesbian women the lowest) and choice dissatisfaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 0 publications
0
19
0
1
Order By: Relevance
“…Despite this emergence, there still remains a paucity of research devoted exclusively to the career development of lesbians (Chung, 2003). Researchers continue to study the career development of lesbians and gay men together, regardless of the assertions from some researchers that sexual minorities should not be treated as a homogeneous group when exploring career-related issues (Elliott, 1993;Etringer, Hillerbrand, & Hetherington, 1990).…”
mentioning
confidence: 99%
“…Despite this emergence, there still remains a paucity of research devoted exclusively to the career development of lesbians (Chung, 2003). Researchers continue to study the career development of lesbians and gay men together, regardless of the assertions from some researchers that sexual minorities should not be treated as a homogeneous group when exploring career-related issues (Elliott, 1993;Etringer, Hillerbrand, & Hetherington, 1990).…”
mentioning
confidence: 99%
“…Thus, out GLB role models may be especially important in the career development of GLB individuals because they can demonstrate how to balance private and public aspects ofselfon the job, they can model confidence with one's selfas a GLB individual in a career, and they can challenge stereotypes about appropriate and inappropriate jobs for GLB individuals (Croteau & Thiel, 1993;Hetherington & Orzek, 1989). In addition, observing career role models who are out at work may help young adults anticipate reactions to and consequences ofpublic disclosures about their sexual orientation in the workplace (Elliott, 1993;Etringer, Hillerbrand, & Hetherington, 1990;Morgan & Brown, 1991).…”
mentioning
confidence: 99%
“…Such an assumption is questionable, however, because gay men encounter issues similar to those of lesbians related to sexual identity, social oppression, intimate relationships and discrimination from their heterosexual co-workers. In fact, Etringer et al (1990) found, when compared with other groups, gay men scored the highest on both career uncertainty and dissatisfaction. A number of factors could lead to such a result, but the finding does raise important questions and highlights the need to clarify the implications of sexual identity for the organizational experiences of gay men.…”
mentioning
confidence: 81%